Impact of a proposed training program to develop agility and its impact on improving the shooting skill of promotion in handball players under 13 years of age - Houafi , faiçal; Bourenane Cherif, mostapha cherif (sports creativity, 2025)
The study aimed to find out the impact of developing the characteristic of agility and its impact on improving the skill of repayment from the upgrade through a proposed training program, The research sample consisted of two control and experimental groups in each group of 17 players, They were chosen by the intended method, Using the experimental method, As tools for the study, two physical and skill tests were relied on, The data were processed statistically by using the SPSS statistical program to interpret the results, which indicated that the proposed training program has a positive effect on the shooting skill of promotion among handball players who are less than 13 years old.